Intralesional gene expression profile of JAK-STAT signaling pathway and associated cytokines in Leishmania tropica-infected patients - Hadifar, Shima; Masoudzadeh, Nasrin; Heydari, Hossein; Mashayekhi Goyonlo, Vahid; Kerachian, Mohammadali; Daneshpazhooh, Maryam; Sadeghnia, Ali; Tootoonchi, Nasim; Erfanian Salim, Reza; Rafati, Sima; Harandi, Ali M. (Frontiers in Immunology, 2024)
The JAK-STAT signaling pathway is a central cascade of signal transduction for the myriad of cytokines in which dysregulation has been implicated in progression of inflammatory and infectious diseases. However, the involvement of this pathway in human cutaneous leishmaniasis (CL) due to Leishmania (L.) tropica warrants further investigation. This study sought to investigate differential gene expression of several cytokines and their associated jakstat genes in the lesions of L. tropica-infected patients by quantitative Real-Time PCR. Further, the expression of five inhibitory immune checkpoint genes was evaluated. Results showed that the gene expression levels of both Th1 (ifng, il12, il23) and Th2 (il4, il10) types cytokines were increased in the lesion of studied patients. Further, elevated expression levels of il35, il21, il27 and il24 genes were detected in the lesions of CL patients. Notably, the expression of the majority of genes involved in JAK/STAT signaling pathway as well as checkpoint genes including pdl1, ctla4 and their corresponding receptors was increased. Our finding revealed dysregulation of cytokines and related jak-stat genes in the lesion of CL patients. These results highlight the need for further exploration of the functional importance of these genes in the pathogenesis of, and immunity to, CL.